Mechanisms and the clinical relevance of complex drug–drug interactions - Roberts AG; Gibbs ME (Dove Medical Press, 2018)
Arthur G Roberts, Morgan E Gibbs Pharmaceutical and Biomedical Sciences, University of Georgia, Athens, GA, USA Abstract: As a result of an increasing aging population, the number of individuals taking multiple medications simultaneously has grown considerably. For these individuals, taking multiple medications has increased the risk of undesirable drug–drug interactions (DDIs), which can cause serious and debilitating adverse drug reactions (ADRs). A comprehensive understanding of DDIs is needed to combat these deleterious outcomes. This review provides a synopsis of the pharmacokinetic (PK) and pharmacodynamic (PD) mechanisms that underlie DDIs. PK-mediated DDIs affect all aspects of drug disposition: absorption, distribution, metabolism and excretion (ADME). In this review, the cells that play a major role in ADME and have been investigated for DDIs are discussed. Key examples of drug metabolizing enzymes and drug transporters that are involved in DDIs and found in these cells are described. The effect of inhibiting or inducing these proteins through DDIs on the PK parameters is also reviewed. Despite most DDI studies being focused on the PK effects, DDIs through PD can also lead to significant and harmful effects. Therefore, this review outlines specific examples and describes the additive, synergistic and antagonistic mechanisms of PD-mediated DDIs. The effects DDIs on the maximum PD response (Emax) and the drug dose or concentration (EDEC50) that lead to 50% of Emax are also examined. Significant gaps in our understanding of DDIs remain, so innovative and emerging approaches are critical for overcoming them. Keywords: inhibition, induction, synergism, additive, antagonism, adverse drug reactions, ADRs